Assessment Nutritional Status of Elderly People at Old Folk Home in Klang Valley: A Cross-Sectional Study - Maisarah Abdul Mutalib; Norhasliza Mohd Noor; Aida Soraya Shamsuddin; Noor Atiqah Aizan Abdul Kadi; Siti Hajar Adam (Management & Science University, 2023)
Background & Aims: Undernutrition has a detrimental effect on health, especially in elderly individuals. Early detection of malnutrition and malnutrition risk allows for timely prevention and initiation of the necessary nutritional support. The study aimed to determine the prevalence of malnutrition among elderly residents at the old folk home in Selangor, Malaysia. Materials and methods: A total of 46 Klang valley nursing facility residents were enrolled for this cross-sectional study. The Mini Nutritional AssessmentShort Form (MNA-SF), 24-hour food recall, Food frequency questionnaire, Habitual physical activity, 24- hours physical activity recall, and anthropometric measurements were used to assess malnutrition by a trained healthcare professional. Results: Of the 46 participants, 41% had adequate nutrition, 11% had malnutrition, and 48% had malnutrition risk. According to BMI, 6.7% of the population was underweight, 35.6% were overweight, 11.1% were obese, and 46.7% were normal weight. The energy consumption was 2453.9 (±421.6) kcal for female residents and 2248.2 (±536.5) kcal for male residents, which was higher than the Recommended Nutrient consumption (RNI). Contrary to the cereals and grains category, it was determined that enough fruits and vegetables were consumed, as advised by the Food Pyramid. Consumption of milk and dairy products was higher than suggested by the Food Pyramid. Among older adults who are sedentary and inactive, results showed a higher incidence of malnutrition than those who were at risk for it. The amount of daily energy consumed surpassed the RNI, and the elderly did not consume enough of the food groups as advised by the Food Pyramid.